2016
DOI: 10.1039/c6cp06648h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent, temperature and pressure on the stability of chiral and perovskite metal formate frameworks of [NH2NH3][M(HCOO)3] (M = Mn, Fe, Zn)

Abstract: We report the synthesis, crystal structure, and thermal, Raman, infrared and magnetic properties of [NHNH][M(HCOO)] (HyM) compounds (M = Mn, Zn, Fe). Our results show that synthesis from methanol solution leads to perovskite polymorphs while that from 1-methyl-2-pyrrolidinone or its mixture with methanol allows obtaining chiral polymorphs. Perovskite HyFe, chiral HyFe and chiral HyMn undergo phase transitions at 347, 336 and 296 K, respectively, with symmetry changes from Pnma to Pna2, P6 to P222 and P6 to P2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 47 publications
(42 reference statements)
2
58
1
Order By: Relevance
“…These increased interactions are often strong enough to cause deformation of the metal formate framework, leading to pressure‐induced phase transitions. Phase transitions associated with distortion of metal formate framework and decrease of the crystal symmetry, were reported for [(CH 2 ) 3 NH 2 ][Zn(HCOO) 3 ], [ND 4 ][Zn(DCOO) 3 ], chiral [NH 2 NH 3 ][Zn(HCOO) 3 ], perovskite [NH 2 NH 3 ][Zn(HCOO) 3 ], [C 3 N 2 H 5 ][Mg(HCOO) 3 ], [NH 3 (CH 2 ) 4 NH 3 ][Zn 2 (HCOO) 6 ], [(CH 3 ) 2 NH 2 ][Mg(HCOO) 3 ], [(CH 3 ) 2 NH 2 ][Cd(HCOO) 3 ], and [(CH 3 ) 2 NH 2 ][Mn(HCOO) 3 ] at 0.4, 1.1, 2, 5.2, 3, 4.1, 2.2 (4.0), 2 (3.6), and 2.1 (4.1) . Upon further increase of pressure, the amine‐formate interactions exhibit further increase, and they may lead to further distortion of the framework and changes in the structure of the protonated amine itself.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These increased interactions are often strong enough to cause deformation of the metal formate framework, leading to pressure‐induced phase transitions. Phase transitions associated with distortion of metal formate framework and decrease of the crystal symmetry, were reported for [(CH 2 ) 3 NH 2 ][Zn(HCOO) 3 ], [ND 4 ][Zn(DCOO) 3 ], chiral [NH 2 NH 3 ][Zn(HCOO) 3 ], perovskite [NH 2 NH 3 ][Zn(HCOO) 3 ], [C 3 N 2 H 5 ][Mg(HCOO) 3 ], [NH 3 (CH 2 ) 4 NH 3 ][Zn 2 (HCOO) 6 ], [(CH 3 ) 2 NH 2 ][Mg(HCOO) 3 ], [(CH 3 ) 2 NH 2 ][Cd(HCOO) 3 ], and [(CH 3 ) 2 NH 2 ][Mn(HCOO) 3 ] at 0.4, 1.1, 2, 5.2, 3, 4.1, 2.2 (4.0), 2 (3.6), and 2.1 (4.1) . Upon further increase of pressure, the amine‐formate interactions exhibit further increase, and they may lead to further distortion of the framework and changes in the structure of the protonated amine itself.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression . Furthermore, application of pressure may lead to discovery of novel polymorphs that are not thermodynamically stable at ambient conditions . We have decided, therefore, to study high‐pressure behaviour of recently discovered acetamidinium manganese formate ([CH 3 C(NH 2 ) 2 ][Mn(HCOO) 3 ], AceMn), using Raman spectroscopy because this method is well‐known to be a very valuable tool in high‐pressure studies due to its sensitivity to changes in dynamics and structure of molecular units …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, an investigation of behavior of MOFs in response to this external stimulus is necessary, especially from the application point of view. Up to date, a few papers reported high pressure studies of chiral, perovskite and niccolite metal formate frameworks. These studies revealed presence of pressure‐induced transformations and negative linear compressibility for some compounds.…”
Section: Introductionmentioning
confidence: 99%